Taxes on the internet. Deterrence effects of public disclosure - Erlend E. Bø; Joel Slemrod; Thor O. Thoresen (Statistics Norway, Research Department, 2014)
Supporters of public disclosure of personal tax information point to its deterrent effect on tax evasion, but this effect has not been empirically explored. Although Norway has a long tradition of public disclosure of tax filings, it took a new direction in 2001 when anyone with access to the Internet could obtain individual information on income, wealth, and income and wealth taxes paid. We exploit this change in the degree of exposure to identify the effects of public disclosure on income reporting. Identification of the deterrence effects of public disclosure is facilitated by the fact that, prior to the shift to the Internet in 2001, some municipalities had exposure which was close to the Internet type of public disclosure, as tax information was distributed widely through paper catalogues that were locally disseminated. We observe income changes that are consistent with public disclosure deterring tax evasion: an approximately 3 percent higher average increase in reported income is found among business owners living in areas where the switch to Internet disclosure represented a large change in access.
Keywords: H24; H26; H30; 330; Tax Evasion; Income reporting; Quasi-experiments